2011
DOI: 10.1038/gene.2010.72
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the murine spleen T-cell cholinergic receptors and their role in in vitro differentiation of naïve CD4 T cells toward the Th1, Th2 and Th17 lineages

Abstract: Acetylcholine (ACh) regulates vital functions of T cells by acting on the nicotinic and muscarinic classes of cholinergic receptors, nAChR and mAChRs, respectively. This study was performed in murine splenic T cells. In freshly isolated CD4 and CD8 T cells, we detected mRNAs encoding a5, a9, a10, b1, b2, b4 nAChR subunits and M 1 , M 3 , M 4 and M 5 mAChR subtypes, whereas a2 was detected only in CD8 T cells. In vitro activation of CD4 T cells through T-cell receptor (TCR)/CD3 cross-linking was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 45 publications
7
73
1
3
Order By: Relevance
“…Such a difference in ␣7 nAChR expression between these two species has also been shown in lymphocytes (8,30,32,39,40), and may underlie a different neuroimmunomodulatory potential of lymphoid cells in them. In mouse, nicotine exposure impairs the ability of NK cells to kill target cells and release cytokines through ␤2-containing nAChRs (29).…”
Section: Discussionmentioning
confidence: 97%
“…Such a difference in ␣7 nAChR expression between these two species has also been shown in lymphocytes (8,30,32,39,40), and may underlie a different neuroimmunomodulatory potential of lymphoid cells in them. In mouse, nicotine exposure impairs the ability of NK cells to kill target cells and release cytokines through ␤2-containing nAChRs (29).…”
Section: Discussionmentioning
confidence: 97%
“…These results differed somewhat from the findings of Qian et al regarding the muscarinic cholinergic regulation of CD4 þ T-cell differentiation. 25 They reported that in vitro stimulation of CD4 þ T-cells with the mAChR agonist muscarine increases IL-17 production and decreases IFN-c secretion without affecting IL-4 levels, and these effects are abolished with the administration of the mAChR antagonist atropine. These in vitro results and our in vivo results demonstrate that mAChR blockade leads to Th17 inhibition; however, the findings regarding Th1 and Th2 responses are not consistent between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Because of a wide variety of nAChR subtypes, details of nAChR subtype expression in each immune cell type are not yet known. However, most immune cells express mRNAs for neuronal type nAChR subunits, though the patterns of nAChR subunit expression vary among animal species and immune cells, and even between developmental stages within a cell [57]. Gene expression for the α3, α5, α7, α9 and α10 nAChR subunits has been commonly detected in human T and B cells [49].…”
Section: Expression Of Achrs In Immune Cellsmentioning
confidence: 98%